THE PECULIARITIES OF THE INCIDENCE OF NON-REFUNDABLE FUNDS IN THE EUROPEAN UNION AND ROMANIA - Florentina Moisescu (Risk in Contemporary Economy, 2013)
In the contemporary period is cardinal, especially for the European citizens, potential and active economic agents, to be aware of the opportunities offered by the unique partnership called European Union. The allocation of funding to European Union member states and their absorption capacity is a current topic of great significance in the context of globalization, so that European cohesion implies the existence of grants and the appearance of inherent controversies. In this way, we considered opportune a comparative study between Romania and the other representative countries. So far, Romania has absorbed only 10% of the total funds provided by the European Union for the financial year 2007-2013. Given the gap with the developed countries of the Community, this percentage is not justified, drawing attention in a negative way towards Romanian state. Thus, this facet of Romania enables us to analyze the issue of low absorption rate of European Union funds. As the next trance of EU funds is coming, scheduled during the years 2014-2020, we intend to illustrate viable, propitious solutions to eradicate vicissitudes for the purpose of building a transparent and competitive environment for accessing grants.